Bimetallic oxygen electrocatalyst derived from metallocenes doped MOFs. (12th March 2021) - Cheng, Guojie; Wu, Guangyao; Li, Han; Liu, Shucheng; Liu, Yi
Abstract: Herein, metallocens (ferrocene, ruthenocene and cobaltocene) were in situ hybridized with two dimensional metal-organic frameworks (MOFs) via an improved inter-diffusion approach. The metallocens@MOFs hybrids were direct carbonized and transformed to Fe(Ru, Co)–Co@C composites. These bimetallic electrocatalysts show remarkable oxygen evolution reaction (OER) activity by taking advantage of the synergetic effect between the binary metals. Among of them, the obtained Fe–Co@C exhibits lower overpotential (320 mV at 10 mA cm −2 ) and satisfactory stability toward OER. The study presents a novel and facile strategy to synthesize low-cost bimetallic catalyst, showing great promise in electrocatalysis of oxygen.